2022
DOI: 10.30574/wjarr.2022.16.2.1071
|View full text |Cite
|
Sign up to set email alerts
|

The influence of leadership style, teamwork and organizational learning on performance through job satisfaction of state vocational school teachers

Abstract: The purpose of this study is to identify and analyze this study to determine and analyze the influence of leadership style on teacher job satisfaction. Teamwork on teacher job satisfaction. Organizational learning affects teacher job satisfaction. Leadership style affects teacher performance. Teamwork affects teacher performance. Organizational learning affects teacher performance. Job satisfaction affects performance. Leadership style affects performance through job satisfaction Teamwork affects performance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…respective roles (Yuniarti, 2022). Schools have interconnected components with each other and work together to achieve common goals (Asrin Randelangi et al, 2022;Qadarsih et al, 2023). It was also added that teachers are a professional group that is considered important in the nation's progress (Verma & Emirates, 2018).…”
Section: Completion Of Studiesmentioning
confidence: 99%
“…respective roles (Yuniarti, 2022). Schools have interconnected components with each other and work together to achieve common goals (Asrin Randelangi et al, 2022;Qadarsih et al, 2023). It was also added that teachers are a professional group that is considered important in the nation's progress (Verma & Emirates, 2018).…”
Section: Completion Of Studiesmentioning
confidence: 99%
“…Policymakers and the managers of the Ghana Education Service should explore the many factors that contribute to teachers' job satisfaction and dissatisfaction, find ways of meeting the needs of teachers, and work hard to influence them to commit to their work. For instance, teamwork and collaborative work environments are identified to have a productive and substantial influence on teacher job satisfaction (Randelangi et al, 2022). It is, therefore, suggested that the Ghana Education Service should strengthen and provide the needed resources for kindergarten teachers to engage in professional learning communities to promote collegiality among teachers, share learning experiences, develop collaborative skills, and enhance their professional competencies and practices.…”
Section: Implications and Future Directionsmentioning
confidence: 99%